The Impact of SARS-CoV-2 Infection on Blood Coagulation and Fibrinolytic Pathways: A Review of Prothrombotic Changes Caused by COVID-19 - Bahraini, Mehran; Dorgalaleh, Akbar (Seminars in Thrombosis and Hemostasis, 2021)
The cardinal pathology of coronavirus disease 2019 (COVID-19) is a primary infection of pulmonary tract cells by severe acute respiratory syndrome coronavirus 2, provoking a local inflammatory response, often accompanied by cytokine storm and acute respiratory distress syndrome, especially in patients with severe disease. Systemic propagation of the disease may associate with thrombotic events, including deep vein thrombosis, pulmonary embolism, and thrombotic microangiopathy, which are important causes of morbidity and mortality in patients with COVID-19. This narrative review describes current knowledge of the pathophysiological mechanisms of COVID-19-associated coagulopathy, with focus on prothrombotic changes in hemostatic mediators, including plasma levels of clotting factors, natural anticoagulants, components of fibrinolytic system, and platelets. It will also highlight the central role of endothelial cells in COVID-19-associated coagulopathy. This narrative review discusses also potential therapeutic strategies for managing thrombotic complications. Awareness by medical experts of contributors to the pathogenesis of thrombotic events in COVID-19 is imperative to develop therapeutics not limited to regular anticoagulants. Instituting cooperation among medical personnel and researchers may lessen this novel virus' impact now, and in the event of recurrence.
Keywords: SARS-CoV-2; COVID-19; coagulopathy; thrombosis